Management of anemia among patients in intensive care units - Margo, Eveline (Universa Medicina, 2008)
Anemia is frequently encountered in critically-ill patients in the intensive care unit (ICU). Anemia may occur both at the time of admission, during treatment and after discharge from the ICU. The causes are multifactorial and include acute blood loss, blood loss from diagnostic testing and blunted red blood cell production. Blood transfusions are frequently given to patients in the ICU to treat low hemoglobin levels due to either acute blood loss or subacute anemia associated with critical illness. Although blood transfusion is a life-saving therapy, evidence suggests that it may be associated with an increased risk of morbidity and mortality. A feature of anemia of critical illness is lack of appropriate elevation of circulating erythropoietin concentrations in response to physiological stimuli. One important concern is that anemia may not be well tolerated by a critically ill patient. A number of blood conservation strategies exist that may mitigate anemia in hospital patients and limit the need for transfusion. These strategies include the use of hemostatic agents, hemoglobin substitutes and blood salvage techniques, the reduction of blood loss associated with diagnostic testing, the use of erythropoietin and the use of restrictive blood transfusion triggers. In this article we review the prevalence of anemia during critical illness specifically among patients in the ICU, and discuss the various factors that contribute to its development, the prevention and treatment of anemia by appropriate red cell transfusion and the place of erythropoietin in treatment.